2020
DOI: 10.34172/ajdr.2020.12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of C-Shaped Canals in Anterior and Posterior Teeth of Iranian Population Using Cone Beam Computed Tomography

Abstract: Background: Lack of knowledge of root anatomy is the second most common reason for failed endodontic therapy. Therefore, acquiring knowledge about it leads to a more effective treatment. C-shaped canal is an anatomical variation that causes clinical challenges. The objective of this study is to determine the occurrence of the C-shaped roots in permanent anterior and posterior teeth of the Iranian population using CBCT (cone beam computed tomography) scans. Methods: This was a descriptive cross-sectional study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In contrast, some other studies did not find a significant difference in the distribution of C-shaped canals between males and females (Janani et al, 2018;Ostevar Rad et al, 2020). The present results were in agreement with the findings of those that did not find a significant correlation between gender and C-shaped canal configuration (Janani et al, 2018;Ostevar Rad et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In contrast, some other studies did not find a significant difference in the distribution of C-shaped canals between males and females (Janani et al, 2018;Ostevar Rad et al, 2020). The present results were in agreement with the findings of those that did not find a significant correlation between gender and C-shaped canal configuration (Janani et al, 2018;Ostevar Rad et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies indicated a higher frequency of C-shaped canals in females (Haddadi et al, 2019;Madani et al, 2017); while some others reported a higher frequency of C-shaped canals in males (Sarraf et al, 2022). In contrast, some other studies did not find a significant difference in the distribution of C-shaped canals between males and females (Janani et al, 2018;Ostevar Rad et al, 2020). The present results were in agreement with the findings of those that did not find a significant correlation between gender and C-shaped canal configuration (Janani et al, 2018;Ostevar Rad et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations